Bleja, Beer, and Bombs: An Exploration into the Inhabited Spaces and Prolonged Youth of a Group of Serbian Young Adults from a Generation Born into a Decade of Conflict and Critical Events - Dončić, Tami (Lidé města, 2023)
This paper aims to explore the worldview of young people in Serbia (defined here as roughly those aged 18–30) who are experiencing prolonged youth due to the repercussions of critical events that shaped their formative years, from the viewpoint of one particular friendship group. By documenting the “nodal points” and rituals of a group of young people in a small Serbian city, utilizing research gathered through a variety of methods, including direct observation, ethnographic participation, and formal interviews, this paper seeks to open a window of understanding to the liminal space occupied by youth in the face of the material and economic forces shaping the sociopolitical background of their lives. This paper also aims to contextualize the current social and economic climate that young Serbians are facing.